Recent Y chromosome divergence despite ancient origin of dioecy in poplars (Populus). Issue 13 (2nd April 2015) - Geraldes, A.; Hefer, C. A.; Capron, A.; Kolosova, N.; Martinez‐Nuñez, F.; Soolanayakanahally, R. Y.; Stanton, B.; Guy, R. D.; Mansfield, S. D.; Douglas, C. J.; Cronk, Q. C. B.
Abstract All species of the genus Populus (poplar, aspen) are dioecious, suggesting an ancient origin of this trait. Despite some empirical counter examples, theory suggests that nonrecombining sex‐linked regions should quickly spread, eventually becoming heteromorphic chromosomes. In contrast, we show using whole‐genome scans that the sex‐associated region in Populus trichocarpa is small and much younger than the age of the genus. This indicates that sex determination is highly labile in poplar, consistent with recent evidence of 'turnover' of sex‐determination regions in animals. We performed whole‐genome resequencing of 52 P. trichocarpa (black cottonwood) and 34 Populus balsamifera (balsam poplar) individuals of known sex. Genomewide association studies in these unstructured populations identified 650 SNPs significantly associated with sex. We estimate the size of the sex‐linked region to be 100 kbp. All SNPs significantly associated with sex were in strong linkage disequilibrium despite the fact that they were mapped to six different chromosomes (plus 3 unmapped scaffolds) in version 2.2 of the reference genome. We show that this is likely due to genome misassembly. The segregation pattern of sex‐associated SNPs revealed this to be an XY sex‐determining system. Estimated divergence times of X and Y haplotype sequences (6–7 Ma) are much more recent than the divergence of P. trichocarpa (poplar) and Populus tremuloides (aspen). Consistent with this, in P. tremuloides, we found no XY haplotype divergence within the P. trichocarpa sex‐determining region. These two species therefore have a different genomic architecture of sex, suggestive of at least one turnover event in the recent past.